ANALISIS DAMPAK LALU LINTAS AKIBAT KEBERADAAN PUSAT PERBELANJAAN ROXY TERHADAP KINERJA RUAS JALAN RAJA DON THOMAS MAUMERE - Wilibrodus Hadiwikarta; Yono Putra (Program Studi Teknik Sipil, 2023)
This research focuses on knowing traffic performance on Raja Don Thomas street as well traffic generation and attraction caused by existence of the Roxy maumere shopping centre on the performance of Raja Don Thomas road. the method used this research was qualitative methods using research techniques in the form observation, experimentation,and open interviews. Data presented in the form of numbers/scale, and in the form of opinions or the results of field record. In conducting data analyisis, the writer used a method namely the multiple linear regression equation method. The equation formula as Y= a-b1X1+B2X2 then, the result multiple regression quation double was Y=10,196- 18,92X1+135,9X2. The results obtained based on data analysis was the Fcount value was 0,008 <Ftable 199 with a sicnificant value of 0,008 <0,05, then how was accepted. Thus, the decision was accepted, and the hypothesis that could be drawn was there was no sicnificant effect between the number of goods (X1) and number of empeloyes (X2) on incoming and outgoing vehicels (Y). Based on the previous data analysis results, the conclision was the analysis performance of the Raja Don Thomas road section was 0,32 with a stable follow B level of service, but the operating speed was beginning to be limited by traffic conditions. The number of vhichels leaving and entering the Roxy Maumere supermarket was unaffected by the number of goods or empeloyes.